The Peruvian Association for Family Protection and Family Planning - Alfaro, Carlos (2015)
The Peruvian Association for Family Protection is a non-profit organization Founded in 1967 to develop activities oriented toward the improvement of the family. They are considered on a health and welfare approach to responsable parenthood. Health measures are directed to children up to school age and mothers in all stages of childbearing. Associated services of Gynecological cancer control, sterility and a comprehensive educational program are part of the general activities. A total of 18,723 women are controlled in the family planning program in a number of medical centers. 57 per cent of all patients are under injectable contraceptive methods.